19.7k views
16 votes
Given that f(x)=2x+1
a) find f(2)
b)find f^-1(x)
c)f^-1(7)

1 Answer

2 votes

Answer:

a)
f(2) = 5, b)
f^(-1) (x) = (x-1)/(2), c)
f^(-1) (7) = 3

Explanation:

a) We evaluate the function at
x = 2:


f(2) = 2\cdot (2) + 1


f(2) = 4+1


f(2) = 5

b) First, we determine the inverse of the function by algebraic means:

1)
y = 2\cdot x + 1 Given

2)
y +(-1) = 2\cdot x + [1+(-1)] Compatibility with addition/Associative property

3)
y + (-1) =2\cdot x Existence of additive inverse/Modulative property

4)
2^(-1)\cdot [y+(-1)] = (2\cdot 2^(-1))\cdot x Compatibility with multiplication/Commutative and associative properties

5)
[y+(-1)]\cdot 2^(-1) = x Existence of multiplicative inverse/Modulative and commutative properties

6)
x = [y+(-1)]\cdot 2^(-1) Symmetry property of equality

7)
x = (y-1)/(2) Definitions of subtraction and division

8)
f^(-1) (x) = (x-1)/(2)
x = f_(-1) (x)/
y = x/Result

c) Now we evaluate the expression obtained on b) at the given number:


f^(-1) (7) = (7-1)/(2)


f^(-1) (7) = 3

User Wes H
by
4.8k points